2012
DOI: 10.1007/s00217-012-1701-3
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin attenuates hyperinsulinemia-induced insulin resistance in skeletal muscle cells

Abstract: Previous studies have shown that hyperinsulinemia is not only a marker of insulin resistance, but also the causative factor of peripheral tissue insulin resistance. It also has been suggested that prolonged high-dose insulin treatment can mimic the effects of hyperinsulinemia and exacerbate insulin resistance in skeletal muscle cells. However, how to prevent or reverse insulin resistance induced by hyperinsulinemia remains largely unclear.In the past few decades, the use of myricetin as an antidiabetic agent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…From our results, myricitrin seems to be a powerful inhibitor of SGLT1 activity and also has alternative sites of action in intestine. Interestingly, these results are additive with antidiabetic effect of myricitrin by acting on aldose reductase and on glucose uptake in C2C12 myotubules under normal and insulin-stimulated conditions [33], suggesting a relevant role of myricitrin on glycemia homeostasis. In our experimental conditions using 10mM of glucose, phlorizin effectively blocked the glucose absorption indicating that SGLT1 is inhibited.…”
Section: Discussionmentioning
confidence: 87%
“…From our results, myricitrin seems to be a powerful inhibitor of SGLT1 activity and also has alternative sites of action in intestine. Interestingly, these results are additive with antidiabetic effect of myricitrin by acting on aldose reductase and on glucose uptake in C2C12 myotubules under normal and insulin-stimulated conditions [33], suggesting a relevant role of myricitrin on glycemia homeostasis. In our experimental conditions using 10mM of glucose, phlorizin effectively blocked the glucose absorption indicating that SGLT1 is inhibited.…”
Section: Discussionmentioning
confidence: 87%
“…Berberine has also been reported to be responsible for moderate inhibition of mitochondrial function, decreased oxygen consumption and enhanced glycolysis which lead to increased AMP/ATP ratio and subsequent activation of AMPK pathway 81 , 154 , 156 . In a study conducted by Ding and his group 157 , myricetin intervention revealed the attenuation for the inhibitory effect of hyperinsulinemia on glucose uptake through increasing AMP-activated protein kinase activity in C2C12 myotubes.…”
Section: Recent Studies On Flavonoids Modulating Glucose Transporter mentioning
confidence: 99%
“…During a drug screening study among 30 bioflavonoids on glucose uptake under normal and insulin-stimulated conditions in C2C12 myotubes, it was found that myricetin was the only compound that stimulated insulin-mediated lipogenesis 52 . The insulin-mimicking effect of myricetin has also been reported on glucose transport in adipocytes of rats with noninsulin-dependent diabetes 53 …”
Section: Antidiabetic Interventions and Plant Polyphenolsmentioning
confidence: 99%
“…An array of health-promoting effects of myricetin has been demonstrated 50, 51. Apart from myricetin's antioxidative, antiviral, and anticarcinogenic activities, consumption of myricetin and reduced risk of diabetes have been reported in many studies 51, 52…”
Section: Antidiabetic Interventions and Plant Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation